KETERLIBATAN LEGISLATOR PEREMPUAN DALAM PEMILU LEGISLATIF DI KOTA LANGSA - Abdullah, Taufik; Alfian, Alfian; Mulyadi, Mulyadi (Program Studi Sosiologi Universitas Malikussaleh, 2023)
This study examines the phenomenon of minimal female representation, the challenge of the 30 percent affirmative action, the urgency of female legislators, the framing of the current context, and the discourse on strengthening gender-sensitive female legislators. Through a qualitative approach, various phenomena are explored descriptively and analytically. The research findings explain that the lack of representation is due to the persistence of patriarchal culture within political parties. Women are often merely seen as a requirement to participate in elections. Weak access and freedom during the campaign season, as well as the fragility of voter networks, are among the factors contributing to the difficulty in meeting female legislative representation. Their election is largely supported by social networks, familial relationships, and family solidarity. The role of legislators is limited to fulfilling formal duties and responding to the demands or needs of constituents. The highlighted articulation is various forms of social and religious action. The conclusion of this study emphasizes that female legislators have yet to substantively influence gender-based policies. The commitment of political parties to fulfilling female representation by nominating potential candidates based on social networks and familial relationships warrants further investigation. This strategy is not impossible; achieving the 30 percent representation of female legislators in the future is feasible.